Detection of Helicobacter pylori in Gastric Mucosa of Patients with Gastroduodenal Diseases by PCR-Restriction Analysis Using the RNA Polymerase Gene (rpoB) - Lim, Chang-Young (American Society for Microbiology, 2003)
A novel PCR restriction analysis method using the RNA polymerase β-subunit- coding gene (rpoB) was employed to both detect and identify Helicobacter pylori in biopsy specimens and culture isolates. The rpoB DNAs (458 bp) were specifically amplified by PCR with the Helicobacter-specific primers (HF and HR). Based on the determined rpoB sequences of the culture isolates, an H. pylori-specific restriction site, Tru9I, was found. H. pylori can be identified by observing two discernible DNA fragments (288 and 138 bp) after Tru9I digestion and agarose gel electrophoresis. The rpoB PCR and subsequent restriction analysis (PRA) enabled the specific detection and identification of H. pylori in biopsy specimens from patients with gastroduodenal diseases. The rpoB PRA conferred a compatible or a slightly higher positive rate (53.7%) than did the Campylobacter-like organism (CLO) test (50.4%) and glmM PCR (48.8%), suggesting that it is useful for diagnosing an H. pylori infection without culture in the clinical laboratory.